2005
DOI: 10.1016/j.pain.2005.06.016
|View full text |Cite
|
Sign up to set email alerts
|

GD3 synthase gene knockout mice exhibit thermal hyperalgesia and mechanical allodynia but decreased response to formalin-induced prolonged noxious stimulation

Abstract: Gangliosides are a family of sialic acid-containing glycosphingolipids that are highly enriched in the mammalian nervous system. In particular, b- and c-series gangliosides, all of which contain alpha-2,8 sialic acids, have been considered to play important roles in adhesion, toxin-binding, neurite extension, cell growth and apoptosis. However, the neurobiological functions of these series of gangliosides remain largely unknown. To clarify the function of b- and c-series gangliosides in pain sensation in vivo,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Another relevant factor, the size of the pool of synaptic vesicles ready for release, is not likely to be influenced by gangliosides, because we did not find differences between genotypes when we assessed for this parameter with hypertonic stimulation (Stevens and Tsujimoto, 1995;Varoqueaux et al, 2005), either here at aged NMJs or previously in younger ones (Zitman et al, 2008). The less steep relationship between extracellular Ca 2+ and evoked ACh release observed at NMJs of old GD3s-KO mice (and seen previously in young ones) may also be due to altered Ca 2+ buffering or membrane flux, possibly resulting from a progressive increase in GM1 density due to accumulation of O-and/or a-series gangliosides (Handa et al, 2005;Okada et al, 2002). This may also explain the higher MEPP frequency at GD3s-KO NMJs in 0.2 and 2 mM extracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Another relevant factor, the size of the pool of synaptic vesicles ready for release, is not likely to be influenced by gangliosides, because we did not find differences between genotypes when we assessed for this parameter with hypertonic stimulation (Stevens and Tsujimoto, 1995;Varoqueaux et al, 2005), either here at aged NMJs or previously in younger ones (Zitman et al, 2008). The less steep relationship between extracellular Ca 2+ and evoked ACh release observed at NMJs of old GD3s-KO mice (and seen previously in young ones) may also be due to altered Ca 2+ buffering or membrane flux, possibly resulting from a progressive increase in GM1 density due to accumulation of O-and/or a-series gangliosides (Handa et al, 2005;Okada et al, 2002). This may also explain the higher MEPP frequency at GD3s-KO NMJs in 0.2 and 2 mM extracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 56%
“…Gangliosides are present in the vicinity of AChRs (Pato et al, 2008) and can interact with the protein, as shown for AChR-rich membrane from Torpedo marmorata (Mantipragada et al, 2003). Accumulation of O-and/or a-series gangliosides may occur at muscle membranes of GD3s-KO mice, as it does at neuronal membranes (Handa et al, 2005;Okada et al, 2002), and progressiveness of this process may lead to the observed age-specific changes in EPP kinetics. EPP rise time and halfwidth are highly temperaturedependent parameters (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, they exhibit reduced regeneration of axotomized hypoglossal nerves as compared to wild-type mice. In addition, ST8Sia-I knockout mice exhibit increased sensory responses to thermal and mechanical stimuli and decreased responses during the late phase of the formalin injection test (115). This suggests that b-and c-series gangliosides are critical in the repair and functional maintenance of the nervous system.…”
Section: F Functions Of the St8sia Family Membersmentioning
confidence: 99%
“…In addition, ST8Sia I knockout mice exhibited increased sensory responses to thermal and mechanical stimuli and decreased responses during the late phase of a formalin injection test. 59) This suggests that b-and c-series gangliosides are critical in the development, maintenance, and repair of the nervous system. Double knockout mice lacking the GM2/GD2 synthase and GD3 synthase genes, which express only the GM3 ganglioside, exhibited lethal audiogenic seizures.…”
Section: The 28-sialyltransferase (St8sia) Familymentioning
confidence: 99%